Role of Pathogens in Multiple Sclerosis. (4th July 2014) - Libbey, Jane E.; Cusick, Matthew F.; Fujinami, Robert S.
<x xml:space="preserve">Abstract</x> Multiple sclerosis (MS) is an inflammatory demyelinating autoimmune disease of the central nervous system (CNS). Although the etiology of MS is unknown, genetic and environmental factors play a role. Infectious pathogens are the likely environmental factors involved in the development of MS. Pathogens associated with the development or exacerbation of MS include bacteria, such as Mycoplasma pneumoniae and Chlamydia pneumoniae, the Staphylococcus aureus-produced enterotoxins that function as superantigens, viruses of the herpes virus (Epstein-Barr virus and human herpesvirus 6) and human endogenous retrovirus (HERV) families and the protozoa Acanthamoeba castellanii. Evidence, from studies with humans and animal models, supporting the association of these various pathogens with the development and/or exacerbation of MS will be discussed along with the potential mechanisms including molecular mimicry, epitope spreading and bystander activation. In contrast, infection with certain parasites such as helminthes (Schistosoma mansoni, Fasciola hepatica, Hymenolepis nana, Trichuris trichiura, Ascaris lumbricoides, Strongyloides stercolaris, Enterobius vermicularis) appears to protect against the development or exacerbation of MS. Evidence supporting the ability of parasitic infections to protect against disease will be discussed along with a brief summary of a recent Phase I clinical trial testing the ability of Trichuris suis ova treatment to improve the clinical course of MS. A complex interaction between the CNS (including the blood-brain barrier), multiple infections with various infectious agents (occurring in the periphery or within the CNS), and the immune response to those various infections may have to be deciphered before the etiology of MS can be fully understood.